The influence of Spanish language on autism spectrum disorder screening: a systematic review. - Morgan, Casie H.; Abdul-Chani, Monica; Sherrod, Gabriela M.; King, Kathryn P.; Guest, Kristi Carter (International Journal of Developmental Disabilities, 2024)
Objective: In the United States, autism spectrum disorder (ASD) is significantly less diagnosed in Spanish-speaking populations compared to other racial/ethnic groups. Structural barriers such as transportation, insurance, and time have been documented within this population. However, many families also report language as a barrier. The present systematic literature review aims to evaluate research findings on the influence of Spanish language and culture on the ASD screening process. Method: Five databases were searched using key words relating to the aim of the paper to identify potential articles to review. Inclusion criteria included: (1) sample of participants diagnosed with ASD/being evaluated for ASD, (2) Latinx populations that included Spanish-speaking participants, (3) a reference to language included as a research aim or study outcome, and (5) a focus on the screening process or measures for ASD. A total of 132 articles were initially identified. Results: After reviewing for inclusion criteria, 22 articles were included. In total, six countries were represented across all included papers. Major themes emerged regarding barriers to care, cultural awareness, translation barriers, intervention, knowledge/awareness, and screener evaluation. Discussion: Findings indicate that language and sociocultural differences can affect knowledge development, communication within healthcare settings, and result in a limited number of translated resources available for the heterogeneous population of Spanish-speakers.